2017
DOI: 10.1016/j.mcn.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Rem2 signaling affects neuronal structure and function in part by regulation of gene expression

Abstract: The central nervous system has the remarkable ability to convert changes in the environment in the form of sensory experience into long-term alterations in synaptic connections and dendritic arborization, in part through changes in gene expression. Surprisingly, the molecular mechanisms that translate neuronal activity into changes in neuronal connectivity and morphology remain elusive. Rem2, a member of the Rad/Rem/Rem2/Gem/Kir (RGK) subfamily of small Ras-like GTPases, is a positive regulator of synapse form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…Likewise, loss of such inhibition leading to increased CaMKII catalytic activity, such as by Rem2 deletion, could lead to widespread changes in cellular structure and function. This is consistent with the many alterations we observe in our past and current studies of Rem2 deletion [51, 54, 55, 67, 7679]. Compellingly, the ability for Rem2 to inhibit CaMKII catalytic activity has already been linked to regulation of dendritic complexity [79].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Likewise, loss of such inhibition leading to increased CaMKII catalytic activity, such as by Rem2 deletion, could lead to widespread changes in cellular structure and function. This is consistent with the many alterations we observe in our past and current studies of Rem2 deletion [51, 54, 55, 67, 7679]. Compellingly, the ability for Rem2 to inhibit CaMKII catalytic activity has already been linked to regulation of dendritic complexity [79].…”
Section: Discussionsupporting
confidence: 88%
“…Rem2 function has previously been shown to be regulated by neuronal activity [51, 54, 67]. Therefore, we investigated whether visual experience was required for Rem2-dependent regulation of segment number.…”
Section: Resultsmentioning
confidence: 99%
“…Our injection strategy causes expression of GFP (AAV-GFP), or expression of GFP and deletion of Rem2 (AAV-GFP-Cre), from a few dozen neurons, while leaving the majority of the circuit unaffected. We previously verified using qPCR that 3–5 days of viral infection is sufficient to delete Rem2 exons 2 and 3 ( Kenny et al, 2017 ), Figure 1A ). Acute cortical slices were then isolated either 4 days post infection (4 d.p.i., Figure 8A left) or 10–12 d.p.i.…”
Section: Resultsmentioning
confidence: 75%
“…Consistent with this model, we performed RNA-sequencing to identify downstream targets of Rem2 ( Kenny et al, 2017 ). We found that the expression of a number of ion channels, important for establishing neuronal excitability, are regulated by Rem2 signaling in an activity-dependent manner ( Kenny et al, 2017 ). We also recently demonstrated that Rem2 is a novel inhibitor of CaMKII catalytic activity ( Royer et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation